UNION POWER IN WAGE BARGAINING: MODEL OF ANALYSIS AND APPLICATION TO THE ARGENTINE CASE (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
Through a cross-industry study that focuses in the Argentinean private sector, we explore trade union power in wage bargaining considering three dimensions: its sources or determinants, union strategies in relation to how to exercise it, and bargaining results. Assuming that, once the influence of each sector´s ability to pay is controlled, relative wage levels would be the best indicators of trade union bargaining power, we analyze through multivariate regression models the effect on relative wages of three determinants of trade union power and of one variable expressing wage bargaining strategies. Power sources considered are the potential scope of a sectoral disruptive trade union action, that depends on each sector´s position in the system of interdependent economic relations (“strategic power”); the evolution of labour demand in each sector; and the associational capacity of trade unions, as reflected in each sector´s unionization rate. Bargaining strategies are gauged by way of unions´ propensity to take industrial action, expressed in the differential incidence of wage-related conflicts. Regression results indicate that, in the Argentinean case, strategic power and associational capacity as much as trade union strategies indeed contribute to explain wage differentials across economic activities. Therefore, these variables are also appropriate indicators for an empirical approximation to trade union power in wage bargaining.
Keywords: Trade union power, Wage determination, Trade unions, Collective bargaining